Pre-combustion CO2 capture by transition metal ions embedded in phthalocyanine sheets - Chen, X. S. (2013)
Transition metal (TM) embedded two-dimensional phthalocyanine (Pc) sheets have been recently synthesized in experiments [M. Abel, S. Clair, O. Ourdjini, M. Mossoyan, and L. Porte, J. Am. Chem. Soc. 133, 1203 (2010)]10.1021/ja108628r, where the transition metal ions are uniformly distributed in porous structures, providing the possibility of capturing gas molecules. Using first principles and grand canonical Monte Carlo simulations, TMPc sheets (TM = Sc, Ti, and Fe) are studied for pre-combustion CO2 capture by considering the adsorptions of H2/CO2 gas mixtures. It is found that ScPc sheet shows a good selectivity for CO2, and the excess uptake capacity of single-component CO2 on ScPc sheet at 298 K and 50 bar is found to be 2949 mg/g, larger than that of any other reported porous materials. Furthermore, electrostatic potential and natural bond orbital analyses are performed to reveal the underlying interaction mechanisms, showing that electrostatic interactions as well as the donation and back donation of electrons between the transition metal ions and the CO2 molecules play a key role in the capture.